Soul as the sole determinant of human personality in Plato and Yoruba traditional thought (2014)
The soul, as a concept, has been a subject of philosophical inquiry in ancient, medieval and modern history of ideas. There is no universal agreement on the nature or purpose of the soul. Thus, the term “soul” has been given various definitions according to the philosophical theories and cultural perspectives in which it is defined. Soul, according to many religious and philosophical traditions, is the “self-aware essence” unique to a particular living being. In these traditions, the soul is believed to incorporate the inner essence of each living being. Both Plato and the Yoruba consider the soul as the immaterial element that, together with the material body, constitutes the human individual. Plato in The Republic presents a tripartite soul which harmonious interaction produces an esteemed human personality. This Plato’s idea mirrors the notion of the Yoruba that a man’s soul is the reflection of his personality. The word ‘soul’ has been investigated from divergent thematic perspectives — invisibility, intangibility, immortality and reclamation — but this paper sets as its task to examine the Platonic and Yoruba presentations of the soul as the sole determinant of human personality